Al-Idārah at-Tanẓīmiyyah Barnāmaj al-Lughah al-Arabiyyah Li Tarqiyati Mahārah al-Kalām - Shalihah, Imroatus; Ferdiansyah, Novan; Arifa, Zakiyah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- This research covers the organization of management and the division of tasks in the Arabic language program at KSK Fathimatuzzahro’ institution. The article aims to provide a clear and concise analysis of program management and task allocation to enhance effectiveness. Design/Methodology/Approach-This study uses a qualitative research approach with descriptive methods. Data collection was carried out using interview, observation and documentation techniques. The data sources of this research are the results of interviews with the head of the institution, the curriculum department, teaching staff and several documents related to organizing activities. Data analysis was carried out using the Milles and Huberman method, namely: data reduction, data presentation, conclusion drawing. Findings- The scientific findings highlight the effective management organization in the Arabic language program at KSK Fathimatuzzahro’ institution, which involves determining and classifying activities, giving authority, selecting teaching staff, creating an organizational structure, and establishing work guidelines through instruction and coordination. The study reveals two levels of structural management: the institution’s management, which centrally coordinates the foreign language program, and the ORDIKA management, which provides a forum for students to develop organizational skills and assist in coordinating the activities of the institutional. Research Limitation/Implications- This research faces limitations due to narrow variable scope and methodological challenges in objectively measuring speaking skill improvements. However, this study provides in depth insights into the Arabic language program at KSK Fatimatuzzahro', offering practical guidance for enhancing students' speaking abilities.